LCA of a multifunctional bioenergy chain based on pellet production. (1st March 2018) - Ruiz, D.; San Miguel, G.; Corona, B.; López, F.R.
Highlights: Low impacts of pellet bioenergy systems on global categories and high impacts on local ones. Energy crops deteriorate an environmental profile due to water use and local impacts. The environmental performance of a pellet making plant is not affected by incorporation of a CHP unit. Using ash as surrogate fertilizer reduces local impacts in the bioenergy chain. Normalized and weighted results using ILCD method are unfavorable for the bioenergy chain. Abstract: This paper investigates the environmental performance of a multifunctional bioenergy chain for the provision of domestic heat using Life Cycle Assessment methodology. The analysis is based on a commercial pellet plant located in Spain and incorporating a Combined Heat and Power system based on Organic Rankine Cycle technology that also produces electricity that is sold to the grid. The base scenario involves using pine wood both from forests and wood processing activities. This situation is compared against a conventional pellet plant with no Combined Heat and Power, using poplar wood from a Short Rotation Coppice plantation and also using the ash produced in the pellet plant as a surrogate fertilizer. The base scenario has also been compared against domestic heat provision from conventional systems based on natural gas, diesel and electricity. The results have shown that the most impacting activities in the life cycle of the bioenergy chain are primarily attributable to the pellet making process, followed by biomass production, biomass transport and finally pellet combustion by the final user. Incorporation of the Combined Heat and Power system to the pellet plant has a very limited influence on the environmental performance of the system since the power generation capacity is very limited and environmental savings from power generation are offset by detrimental effects associated with extra biomass consumption. For a conventional pellet plant, the normalized impact value obtained using International Reference Life Cycle Data System methodology is 2.78 E−04 µPt (vs 2.85 E−04 µPt for the base scenario). A similar bioenergy chain based on poplar wood from a Short Rotation Coppice generates higher environmental impact in water resource depletion. This impact category has a decisive weight after normalization, making this alternative highly unfavorable (5.50 E−04 µPt). Utilizing the ash fraction produced in the pellet plant as a surrogate fertilizer implies low environmental benefits (2.71 E−04 µPt). When compared against heating systems based on diesel, natural gas or electricity (heat pump), the pellet system benefits from reduced impacts on global impact categories like climate change, ozone depletion and Cumulative Energy Demand. However, the bioenergy system performs worse on local impact categories such as particulate matter formation, human toxicity, photochemical ozone formation, freshwater eutrophication and land use. Normalized impact values suggest that the bioenergy system is the least favorable environmental option (2.85 E−04 µPt) as compared to heating systems based on diesel, natural gas or electricity (5.72 E−05 µPt, 5.15 E−05 µPt and 1.99 E−04 µPt respectively).